2020
DOI: 10.3390/agriculture10050147
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leonardite-Derived Amendments on Soil Microbiome Structure and Potato Yield

Abstract: Humic substances originating from various organic matters can ameliorate soil properties, stimulate plant growth, and improve nutrient uptake. Due to the low calorific heating value, leonardite is rather unsuitable as fuel. However, it may serve as a potential source of humic substances. This study was aimed at characterizing the leonardite-based soil amendments and examining the effect of their application on the soil microbial community, as well as on potato growth and tuber yield. A high yield (71.1%) of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…Similar to our results, there are other welldocumented reports of improved yields of a range of crops from typical application rates (10-40 t ha -1 ) of FYM, BCW and BIO (Shakoor et al 2015;Eprikashvili et al 2016;Faloye et al 2017;Akimbekov et al 2020), although some have reported remote or negative yield responses (Diacono and Montemurro 2011;Tahir et al 2011;Jeffery et al 2017;Chen et al 2018;Kováčik et al 2016). From a range of crops grown in acidic soils, it was reported that biochar amendment led to a median yield increase of 20% (Jeffery et al 2017), while compost amendment resulted in maximum yield increases of 13.6%, and thus the mean increases in yields of maize, potato and barley from FYM (32.7%), BCW (33.5%) and BIO (21.8%) amendments in this study compare well.…”
Section: Crop Yieldsupporting
confidence: 92%
“…Similar to our results, there are other welldocumented reports of improved yields of a range of crops from typical application rates (10-40 t ha -1 ) of FYM, BCW and BIO (Shakoor et al 2015;Eprikashvili et al 2016;Faloye et al 2017;Akimbekov et al 2020), although some have reported remote or negative yield responses (Diacono and Montemurro 2011;Tahir et al 2011;Jeffery et al 2017;Chen et al 2018;Kováčik et al 2016). From a range of crops grown in acidic soils, it was reported that biochar amendment led to a median yield increase of 20% (Jeffery et al 2017), while compost amendment resulted in maximum yield increases of 13.6%, and thus the mean increases in yields of maize, potato and barley from FYM (32.7%), BCW (33.5%) and BIO (21.8%) amendments in this study compare well.…”
Section: Crop Yieldsupporting
confidence: 92%
“…that we found as constituents of the core seed microbiome. Microbiome changes following leonardite treatment have already been studied in other plants, such as grapevine and potato ( Cappelletti et al, 2016 ; Akimbekov et al, 2020 ). Also, Moreno et al (2017) observed an increase of Gram-negative bacteria, such as Proteobacteria , as a consequence of the application of leonardite in barley.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial OM contents were measured in the Cd-Leo and Com-Ctrl treatments (10.2% and 11.7%, respectively), whereas lowest OM content was in the Cd-Alon treatment (3.4%). Humic substances originating from organic matter in leonardite can improve the physicochemical properties of soil and stimulate plant growth performance 19 . Rehman et al 20 indicated that increased OM content in amendments, applied in different combinations, could increase rice growth when high Cd-contaminated effluent water is applied to soil during planting.…”
Section: Resultsmentioning
confidence: 99%